QIRĀAH MAKKAH (STUDI ANALISIS BACAAN IBN KATSĪR AL-MAKKῙ) - Qoriah, Qoriah; Safitri, Tia; Soekarno Putri, Ernawati; Hikmah, Jawahirotul; Zakka, Umar (Jurnal Ushuluddin, 2025)
The Makkan Qira'ah is one of the seven recognized and widely accepted Qur'anic reading traditions (qira'at) acknowledged by Muslim scholars. This qira'ah originates from Imam Ibn Kathir, one of the seven well-known Imams of Qur'anic recitation whose method has served as an important reference in the study of qira'at. The Makkan Qira'ah is distinguished by its unique articulation of letters and its particular style of recitation, which sets it apart from other qira'at. By the early second century Hijri, Muslim communities began to adopt specific qira'at according to their regions, and the people of Makkah chose the qira'ah of Ibn Kathir. This qira'ah has a strong and well-established chain of transmission (sanad) and falls within the category of mutawatir recitations, meaning that it has been transmitted by numerous reliable narrators. This study aims to examine the unique characteristics of the qira'ah of Ibn Kathir al-Makki, to explore his chain of transmission and narrators, and to identify the differences between his two most prominent transmitters, al-Bazzi and Qunbul. The research employs a qualitative approach using library-based methods, gathering data from various classical sources. A descriptive-analytical method is adopted to systematically discuss the historical development of the qira'ah of Ibn Kathir al-Makki as well as its defining features. The findings reveal that one of the characteristics of Ibn Kathir's qira'ah is that he does not apply saktah in the four known places in the Qur'an; instead, he recites them with waqf and idgham. Another prominent feature of his recitation, besides the treatment of saktah, is his frequent use of tashil, particularly when encountering two hamzahs in succession when the first carries a fathah and the second a kasrah or ḍammah, he applies tashil. Meanwhile, the differences between the readings of his two transmitters can be seen, for example, when encountering two hamzahs that both carry ḍammah: al-Bazzi eases (yutas-hil) the first hamzah, while Qunbul eases the second. This study highlights the importance of understanding the characteristics and sanad of Ibn Kathir's qira'ah in order to deepen knowledge of the qira'at. Since the qira'ah of Ibn Kathir is mutawatir, it may be used as a valid reference for reciting the Qur'an, including during prayer.